The Comparison Between Students’ Writing Achievement In Private and State of Junior High School - Putri, Riska Maharani; Prihatin, Yoga; Yuvita (South Asian Journal of Social Sciences and Humanities, 2020)
The objectives of this Research Project are to find out the differences between students’ writing  achievement in state and private of junior high school and to identify the motivating factors that  influence the difference between students’ English learning. The research method used is MMR  (Mixed Method Approach). There are 66 students as the sample, 33 students from state and private  school. The researcher analysis data by using t-test and questionnaire. The sig. 2-tailed is 0,012 while  the significant level is at 5% level significance, which is 0,05. It indicates that there is a difference  between students’ writing achievement in state and private school because the significance 2-tailed is  less than the significant level (0,012 < 0,05). After the researcher analyzed the t-test, the researcher  analyzed the questionnaire. The questionnaire is divided into two, internal factors and external factors.  About 59% state school respondents gives positive responses toward internal factors while there is  51% private school respondents gives positive responses toward external factors.
Keywords: Type of Schools; Students’ Writing Achievement; Students’ Motivation